Personal identity development in cultural context: The socialization of master narratives about the gendered life course. (March 2020) - McLean, Kate C.; Boggs, Samantha; Haraldsson, Kristin; Lowe, Alexandra; Fordham, Chelsea; Byers, Staci; Syed, Moin
The present studies focused on the role and socialization of biographical master narratives – cultural narratives that prescribe the types and ordering of events that should occur in one's personal life identity narrative – by focusing on adolescent and emerging adult gender identity development. We employed a combined explanatory and triangulation mixed methods design. Study 1a ( n = 414) was a survey study examining the expected biographical master narrative events for men and women, and the content of master narrative deviation and conformity in an emerging adult sample. In Study 1b ( n = 14) we interviewed participants from Study 1a about their conformity and deviation narratives, as well as their socialization experiences regarding gendered biographical master narratives. In Study 2 mothers and adolescents ( n = 11 pairs), engaged in conversation about expected life course events, as well as a follow-up interview about their conversation. We first found that there are more gender differences in the personal experiences of conformity to and deviation from master narratives compared to the expectations of the life course (Study 1a). Second, deviating is related to more engagement in identity processes (Study 1a). Third, emerging adults report contradictions in retrospective reports of socialization messages regarding expectations (Study 1b), a finding confirmed in a discourse analysis of mothers and their adolescents (Study 2). Overall, across the studies, we see that (a) adolescents and emerging adults are engaged in a delicate balance of negotiating between various cultural and familial messages, as well as personal experiences, about gender identity particularly in regards to gender equality and, (b) there is a complex relation between socialization messages about gender equality that may make some biographical master narratives about the expected life course events for men and women more resistant to change.